Mabar geo learning tool for advancing sustainable education: Enhancing student learning outcomes - Ningrum Epon; Pamungkas Totok Doyo; Pratama Caca Hinaya (E3S Web of Conferences)
Teachers still rarely use ICT-based learning media in the learning process. This research aims to examine the current state of learning outcomes and preparedness in SMA schools in Merauke, Papua with utilize a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis framework and develop the MaBar Geo application for advance sustainable education and analyze its effect on student learning outcomes. This research uses a quasi-experiment method with a one-group pre-test and post-test design. The research results show that 1)The development of the MaBar Geo application received an average score with the category very suitable for use in the learning process after receiving validation from media experts, material experts, and students. 2)Learning outcomes in the experimental class consist of cognitive, affective, and psychomotor aspects, with the highest score in the affective aspect. The results of learning completion were 27 students (75%) classified as complete and 9 students (25%) classified as incomplete. 3) The use of the MaBar Geo application has a positive effect in improving learning outcomes in the experimental class, which is based on the results of the linear regression test with Sig 0.000 < 0.05 and t count (8.504) > t table (1.668).